Long-term monitoring projects of Brazilian marine and coastal ecosystems - Cordeiro, Cesar A.M.M.; Aued, Anaide W.; Barros, Francisco; Bastos, Alex C.; Bender, Mariana; Mendes, Thiago C.; Creed, Joel C.; Cruz, Igor C.S.; Dias, Murilo S.; Fernandes, Lohengrin D.A.; Coutinho, Ricardo; Gonçalves, José E.A.; et al. (PeerJ, 2022)
Biodiversity assessment is a mandatory task for sustainable and adaptive management for the next decade, and long-term ecological monitoring programs are a cornerstone for understanding changes in ecosystems. The Brazilian Long-Term Ecological Research Program (PELD) is an integrated effort model supported by public funds that finance ecological studies at 34 locations. By interviewing and compiling data from project coordinators, we assessed monitoring efforts, targeting biological groups and scientific production from nine PELD projects encompassing coastal lagoons to mesophotic reefs and oceanic islands. Reef environments and fish groups were the most often studied within the long-term projects. PELD projects covered priority areas for conservation but missed sensitive areas close to large cities, as well as underrepresenting ecosystems on the North and Northeast Brazilian coast. Long-term monitoring projects in marine and coastal environments in Brazil are recent (<5 years), not yet integrated as a network, but scientifically productive with considerable relevance for academic and human resources training. Scientific production increased exponentially with project age, despite interruption and shortage of funding during their history. From our diagnosis, we recommend some actions to fill in observed gaps, such as: enhancing projects’ collaboration and integration; focusing on priority regions for new projects; broadening the scope of monitored variables; and, maintenance of funding for existing projects.
Keywords: Ecology; Ocean decade; ILTER; Conservation; Ecosystem management